STRUCTURE OF READINESS FUTURE SOCIAL WORKERS TO PROFESSIONAL ACTIVITY IN INSTITUTIONS OF SOCIAL SERVICES FOR THE ELDERLY - Pavlyshyna, Nataliia B. (Educological discourse, 2014)
In the article discusses the features of formation of future social workers for professional careers in institutions of social services for the elderly; the analysis of the structural components of future social workers to work with customers of gerontology group; characterized motivational, cognitive, operational and personal components of future social workers for professional careers in institutions of social services for the elderly.